WHEN ECONOMISTS FALL IN LOVE: A PERSPECTIVE ON PARTNER SELECTION (Third Sector Social Economic Review, 2022)
The study discusses love and the process of choosing a partner which has been in focus by many disciplines for centuries utilizing economic and mathematical literature while focusing on the evolution of the process, its similarities and differences with markets in economics along with potential risks and positive outcomes. Based on Becker's theory of marriage and the economic infrastructure he used to model it on, possible mechanisms and problems that may arise during partner selection is evaluated as an optimization problem, introducing optimal stopping method as a mathematical approach taking the similarities and differences in today’s world with Becker's analysis focusing on the issues that arose with digitalization. Even if economic models are not sufficient to explain the most basic variables from time to time, the emphasis is on the fact that such romantic markets actually act similarly to economic markets and may be affected by similar disruptions while the way of economic thinking may offer some important takeaways about the structure of individuals' preferences and how their priorities are established. As developments in technology continue to accelerate and changes inevitably affect individuals’ habits, this study is a first in Turkish literature with the perspective taken within this framework.
Keywords: partner selection; marriage theory; optimal stopping; digitalization; imperfect competition